2005
DOI: 10.1111/j.1346-8138.2005.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Linear IgA Bullous Dermatosis

Abstract: We report the case of a 69-year-old Japanese woman with multiple blistering lesions covering almost her whole body. Linear IgA and C3 depositions were seen at the basement membrane zone on direct immunofluorescence (IF). Linear IgA bullous dermatosis (LABD) is one of the autoimmune diseases resulting in subepidermal blisters. It is clinically similar to bullous pemphigoid and IF is required to distinguish the two diseases. In this case, the blistering lesions appeared after vancomycin treatment. This drug was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 51 publications
2
32
0
3
Order By: Relevance
“…Several drugs have been implicated as the cause of LABD, vancomycin being the most frequent [6][7][8][9][10][11][12] . LABD can occur anytime from 1 day to 1 month following the initial administration of vancomycin 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several drugs have been implicated as the cause of LABD, vancomycin being the most frequent [6][7][8][9][10][11][12] . LABD can occur anytime from 1 day to 1 month following the initial administration of vancomycin 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although LABD is usually idiopathic, it may be induced by drugs, malignancies, or infections. Many drugs, such as acetaminophen 2 , amiodarone 3 , furosemide 4 , and phenytoin, 5 have been implicated as the cause; however, vancomycin has been found to be the one most commonly associated 6 . To our knowledge, there have been two cases of vancomycin-induced LABD reported in Korea to date.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, reports have shown that as many as two-thirds of all occurrences may be druginduced. The most frequently implicated drugs were antibiotics, especially vancomycin, penicillin, amoxicillin-clavulanate, cephalosporin, sulfonamides, sulfamethoxazole/trimethoprim, non-steroidal antiinflammatory drugs such as diclofenac, naproxen, piroxicam, antihypertensive drugs such as captopril, angiotensin converting enzyme inhibitor (ACE), and diuretics (10).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports describing association of LABD with various drugs. 4 The most common offending drug has been vancomycin. 4,5 Drug-induced LABD has some differences when compared to the idiopathic variant.…”
mentioning
confidence: 99%
“…4 The most common offending drug has been vancomycin. 4,5 Drug-induced LABD has some differences when compared to the idiopathic variant. The drug-induced type tends to show the transient nature of the cutaneous symptoms, lack of mucosal or conjunctival lesions, and rapid improvement after discontinuation of the medication, and lack of circulating IgA antibodies.…”
mentioning
confidence: 99%